Pengaruh Brand Image dan Persepsi Harga terhadap Keputusan Pembelian Produk Iphone di Wilayah Gubeng Surabaya - Nuruni Ika Kusuma W; Mawan Januar Pratama (J-MAS (Jurnal Manajemen dan Sains), 2022)
The rapid development of today's technological era affects the decision of people who want to buy goods to consider a brand first because of the image that is already attached to the brand, such as quality and price. The number of smartphone products that enter the market for sale today makes consumers make several considerations when choosing a smartphone. Formation of a good iPhone brand image, consumers will consider making purchases on iPhone products, therefore even though the data above shows that the iPhone in 2019-2020 has declined, it does not affect consumer decisions to purchase products. Iphone products have a very good brand image, therefore the price is not a problem for consumers to make purchasing decisions. This study uses a questionnaire method to take samples, researchers will examine iPhone customers in Gubeng Surabaya more than once. Analysis of the data used in this study using the component-based Structural Equation Modeling (SEM) method using Partial Least Square (PLS) analysis tool. The choice of using the PLS analysis tool is because it is widely used for causal-predictive analysis and is an appropriate technique used in prediction applications and theory development in this study. This study obtained the results that brand image and price perception have a positive and significant influence on purchasing decisions on iPhone products in Surabaya.